Health emergency and impermanence - Giuseppe De Giovanni (Agathón)
Answering immediately to a reality increasingly oriented towards quick consumption has originated an architecture highly oriented to the production of temporary and mobile artifacts. The project seizes time and controls its status, becoming a fundamental tool to respond to a continuously evolving reality, often subject of violent and quick transformations, as the ones caused by natural disasters and migrations, resulting from wars or political traumas, giving rise to new forms and systems belonging to a Temporary Architecture that we might call Healthcare. Health Emergency is a reality in our planet’s political, economic and social scene and finds its meaning in emergency for men and caused by man that does not own a cultural and material identity any more but wanders looking for territories that could host him and recognize his right to live.